2017
DOI: 10.1371/journal.pone.0174568
|View full text |Cite
|
Sign up to set email alerts
|

Effects and mechanisms of auricular electroacupuncture on gastric hypersensitivity in a rodent model of functional dyspepsia

Abstract: BackgroundFunctional dyspepsia (FD) is a common functional gastrointestinal disease, and abdominal pain is one of the main symptoms. The aim of this study was to explore the effects and mechanisms of auricular electro-acupuncture (AEA) on gastric hypersensitivity in a rodent model of FD.MethodsTen-day-old pups were gavaged with 0.2 ml of 0.1% iodoacetamide daily for 6 days. AEA at the “stomach” point with different parameters or sham-EA was performed on 8-week-old animals. Gastric sensitivity to gastric disten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
29
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 42 publications
2
29
0
Order By: Relevance
“…These parameters have been shown to reduce gastric hypersensitivity 20 and ameliorate visceral pain in a rodent model of functional dyspepsia. 21 From Figure 7, it is clear that abdominal surgery induced pain, but the pain gradually subsided because there was a significant decrease in the RGS score: pain score starting at 2 hours after the surgery in the control rats. IM, however, delayed this pain recovery by 1 hour; the decrease in the pain score was significant only at 3 hours after the surgery.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…These parameters have been shown to reduce gastric hypersensitivity 20 and ameliorate visceral pain in a rodent model of functional dyspepsia. 21 From Figure 7, it is clear that abdominal surgery induced pain, but the pain gradually subsided because there was a significant decrease in the RGS score: pain score starting at 2 hours after the surgery in the control rats. IM, however, delayed this pain recovery by 1 hour; the decrease in the pain score was significant only at 3 hours after the surgery.…”
Section: Discussionmentioning
confidence: 95%
“…9,10,13,14,17 EA at PC6 was used to mainly provide an analgesic effect and the best stimulation parameters to reduce visceral pain were: on time of 0.1 seconds, off time of 0.4 seconds, 0.5 milliseconds, 100 Hz, and 1 mA. 20,21 Sham-EA was performed in Sham-EA rats. The procedure was the same as EA without electrical stimulation.…”
Section: Electroacupuncture and Sham-electroacupuncturementioning
confidence: 99%
“…[ 27 ] Zhou J et al found that auricular EA can improve the gastric sensitivity of FD rats by improving the balance of sympathetic vagus nerve. [ 24 ] Various clinical studies have reported that the improvement effect of EA on gastric dysrhythmia is consistent and repeatable, suggesting that EA has a strong effect on the treatment of gastric slow-wave dysrhythmia. [ 28 30 ]…”
Section: Discussionmentioning
confidence: 99%
“…A few major mechanisms involved in the analgesic effect of EA on visceral pain or hypersensitivity have been reported: sensory afferent mechanisms involving dorsal root ganglions and opioid mechanisms and vagally mediated mechanisms . It should also be noted that EA stimulation parameters for treating visceral pain may be distinctly different from those used for treating gut dysmotility …”
Section: Mechanisms Of Electroacupuncturementioning
confidence: 99%
“…38 It should also be noted that EA stimulation parameters for treating visceral pain may be distinctly different from those used for treating gut dysmotility. 21,39…”
Section: Mechanis Ms Of Elec Troacupun C Turementioning
confidence: 99%